Cross-border Healthcare: Iceland´s capacity to shape EU legislation on cross-border healthcare as an EFTA-EEA state - Hulda Gísladóttir 1979- (2016)
Skilað eftir útskrift með leyfi deildar. The objective of this research paper was to study how the EFTA-EEA state Iceland functions within the two pillar system of the EEA Agreement. More specific, to review firstly, which opportunities the state has to influence EU Directives that are at a later state implemented into Icelandic national law and secondly how the state uses those opportunities. For this purpose, the Directives on cross-border healthcare were chosen for three reasons; Firstly, they were in the implementation process when this paper was being written; Secondly, with them, the EU law are reaching into new fields formerly under the authority of each member state; And thirdly, they concern us all as they concern the healthcare systems of the EEA member states. The conclusion is that Iceland has narrow chances to influence the shaping of EU law at the legislative proposals preparation phase, and in this specific case, those chances were not used due to limited administrative capacity. The structure of the EEA Agreement in itself makes it difficult for Iceland to influence EU-EEA decision making as neither Icelandic ministers nor parliamentarians are partakers in the day-to-day decision making framework of the EEA institutions. Which leaves the handling of the EEA legislation to a great extent in the hands of decision makers within the EU institutions as well as with Icelandic civil servants. Althingi’s only change to raise concerns is at the final stages of the EU-EEA decision-making process and the EEA bodies are largely unknown to the public. Yet, Iceland is implementing Directives, that are established by the European legislator at a supranational level and has narrow changes to influence them although they are enforced at the national level at a later stage. It was substantiated that lawmaking that happens without Icelandic representation within the EEA, is a norm. This has been described as the self-inflicted hegemony of the EU’s associated non-member states. The new law on cross-border ...